The Effects of Faculty Calibration on Caries Risk Assessment and Quality Assurance. Issue 11 (1st November 2016) - Goolsby, Susie P.; Young, Douglas A.; Chiang, Harmeet K.; Carrico, Caroline K.; Jackson, Leonard V.; Rechmann, Peter
Abstract : Accurate caries risk assessment (CRA) plays a pivotal role in managing the disease of dental caries. The aim of this quality assurance study was to determine if faculty calibration training using a specific set of guidelines in a single session would improve the faculty members' CRA decision making. A calibration seminar was held in December 2014 at the Virginia Commonwealth University School of Dentistry, during which seven completed CRA forms for simulated patients were used to test 55 faculty members' risk assignment level before and after an instructional lecture was given. The results showed a statistically significant increase in the proportion of faculty members responding correctly for five of the seven cases on the pre‐ and posttests (p<0.01). One case showed no significant increase in correct responses (p=0.07), and on the seventh case, which presented low caries risk, there was a significant decrease in the percentage responding correctly (p<0.0001) due to an increase in the proportion overestimating caries risk. This study's findings were consistent with those in previous studies that, without calibration, faculty members are not necessarily accurate at CRA diagnosis. Since the calibration training improved these faculty members' caries risk assessment scoring, future studies should extend to evaluations for both faculty and students.